1984
DOI: 10.1007/bf00517315
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation by hypokalemia of the effects of acetylcholine on the canine heart in situ

Abstract: In the heart in situ of vagotomized dogs, atrioventricular conduction was studied by the His bundle potential recording, sinus rate continuously registered and the effective refractory period (ERP) of the atrial muscle measured by the extrastimulus method. The modifications induced by the acute lowering of plasma potassium concentration from 3.5 to 2.0 mmol/l obtained by hemodialysis appeared to be similar to those due to parasympathetic stimulation and the effects of hypokalemia and acetylcholine (ACh) on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Increased parasympathetic activity has been associated with an increased conduction delay ( Martin, 1977 ); studies in dogs reported an increased conduction delay with acetylcholine administration ( Priola et al, 1983 ; Bertrix et al, 1984 ) and vagal stimulation ( Spear and Moore, 1973 ; Martin, 1975 ; Pirola and Potter, 1990 ). Moreover, there are indications that an increased parasympathetic activity is associated with an increased refractory period ( Martin, 1977 ); experimental studies using rabbit hearts reported an increased AV-nodal refractory period ( West and Toda, 1967 ) and occurrences of 2:1 AV nodal block ( Cranefield et al, 1959 ) with acetylcholine administration, and studies in dogs reported occurrences of AV block with acetylcholine administration ( Hageman et al, 1985 ) and vagal stimulation ( Spear and Moore, 1973 ; Hageman et al, 1985 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased parasympathetic activity has been associated with an increased conduction delay ( Martin, 1977 ); studies in dogs reported an increased conduction delay with acetylcholine administration ( Priola et al, 1983 ; Bertrix et al, 1984 ) and vagal stimulation ( Spear and Moore, 1973 ; Martin, 1975 ; Pirola and Potter, 1990 ). Moreover, there are indications that an increased parasympathetic activity is associated with an increased refractory period ( Martin, 1977 ); experimental studies using rabbit hearts reported an increased AV-nodal refractory period ( West and Toda, 1967 ) and occurrences of 2:1 AV nodal block ( Cranefield et al, 1959 ) with acetylcholine administration, and studies in dogs reported occurrences of AV block with acetylcholine administration ( Hageman et al, 1985 ) and vagal stimulation ( Spear and Moore, 1973 ; Hageman et al, 1985 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, studies on isolated, perfused murine [65] guinea‐pig [66–68] and rabbit heart preparations [69,70] show that APD prolongation in hypokalemic setting may be associated with shortened rather than lengthened refractoriness. Likewise, hypokalemia reduces the ERP in atrial muscle [71–74], wherein it may also exaggerate acetylcholine‐induced shortening in refractoriness. These changes increase vulnerability to tachyarrhythmias because of reduced excitation wavelength [73–75], which enables to fit more re‐entrant circuits into available mass of cardiac tissue.…”
Section: Ventricular Repolarizationmentioning
confidence: 99%
“…Low extracellular K + concentrations contribute to slowed conduction in various parts of cardiac conduction system as well as contractile muscle. Hypokalemia markedly slows atrioventricular (AV) nodal conduction in canine [71,72] and rabbit heart [78], both via direct effect on AV node and because of potentiation of acetylcholine‐induced negative dromotropic responses. Furthermore, hypokalemia has been found to reduce impulse propagation velocity in isolated rabbit atrium [74], sheep Purkinje fibers [92] and cat papillary muscle [93].…”
Section: Conduction Abnormalitiesmentioning
confidence: 99%